Evaluasi Pengelolaan Laboratorium Komputer di SMKN Keahlian TKJ Kota Padang - Mardhiah Masril; Ambiyar; Fahmi Rizal (Cakrawala: Jurnal Pendidikan, 2020)
Goals evaluation research is to illustrate the effectiveness of laboratory computer management in TKJ majors in SMKN Padang City in terms of context, input, process, and product dimensions. In this evaluation research approach with a quantitative descriptive approach. The evaluation model implemented is the evaluation of the CIPP model: Context, Input, Process, Product. The method used is a survey method and data collection tools such as questionnaires, observation sheets, and documentation. Research informants consisted of 4 Principal of SMKN, 4 Vice Principals in the field of Sarpras, 4 Head of TKJ, 4 Head of Lab. Computers, 21 TKJ teachers, and 168 TKJ students of class XI in the 2018/2019 school year. The results of research at the TKJ Department in Padang City Vocational School said that: (1). In terms of context, the effectiveness of laboratory computer management in very good condition with the achievement of a percentage score of 86.96%; (2). In terms of input, the effectiveness of laboratory computer management is in very good condition with an average score of 86.46%; (3). In terms of the process effectiveness of laboratory computer management in good condition with an average score of 7.0%; and (4). In terms of product effectiveness the management of laboratory computers in good condition with an achievement score of 77.06%